Una Via Principle: Legal Certainty and Justice in The Resolution of Capital Market Criminal Cases - Putri Amaris, Putu Kanitha; Yudistira Darmadi, A.A. Ngurah Oka (Westscience Press, 2025)
The focusing aims of this research are to scrutinize and assess the characteristics of capital market crimes that are specifically regulated separately from general crimes in the Criminal Code and the setting of the una via principle in the settlement of capital market crimes in purpose to maintain legal certainty and justice. The problems that underlies include: (1) how is the arrangement of una via principle in Indonesian capital market legal system and (2) how should the application of una via principle in capital market criminal case settlement in Indonesia. With a normative juridical method, this research analyzes norms, principles and legislation related to the una via principle in capital market regulations in Indonesia, namely Law Number 8 of 1995 concerning Capital Markets and Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector. The conclusion drawn from this study indicate the existence of una via principle comes with the concept of selecting sanctions for perpetrators of capital market crimes aimed at providing justice and legal certainty. However, the regulation of the una via principle still needs to be improved because the current legal rules have vagueness which causes unclear procedures for resolving capital market criminal cases. Efforts are needed to improve regulations, increase coordination and collaboration between law enforcement officials, establish a transparent mechanism for imposing sanctions and conduct a transparent and fair trial.